1. X and Y invest Rs.21000 and Rs.17500 respectively in a business. At the end of the year, they make a profit of Rs.26400. What is the share of X in the profit? | |

A. Rs.14400 | B. Rs.26400 |

C. Rs.12000 | D. Rs.12500 |

Here is the answer and explanation

Answer : Option A

Explanation :

Ratio of the investment = 21000 : 17500 = 210 : 175 = 42 : 35 = 6 : 5

Share of X in the profit = 26400 * (6/11) = 2400 * 6 = 14400

ajmal

2016-07-15 06:40:27

another method

investment of x=21000

investment of y=17500

total=38500

% of x = 21000*100/38500 = 54.5454% (∵ comes from 38500*(x/100)=21000)

profit=26400

Share of x = 26400*54.55% =14401

investment of x=21000

investment of y=17500

total=38500

% of x = 21000*100/38500 = 54.5454% (∵ comes from 38500*(x/100)=21000)

profit=26400

Share of x = 26400*54.55% =14401

Saurabh Sarkar

2016-04-24 15:59:24

Stupid question to ask but how did we get 42 : 35 from 210 : 175

Sumathi.R

2015-11-13 06:41:51

X investment=21000=1.2

Y investment=17500=1

so X share is 26400/2.2*1.2=14400

*[(21000/17500)=1.2]*Y investment=17500=1

*(we are assuming 17500/17500=1)*so X share is 26400/2.2*1.2=14400

*[1.2+1=2.2]*
CHANDAN DORA

2014-02-09 06:28:53

i understood clearly using these comment. Thank you all of you.

Shankar

2013-08-13 20:04:30

Assume

then a = 10 * 6/11 and b = 10 * 5/11 where 11 = 6+5

In this question, investment of X : investment of Y = 6 : 5

Hence, Profit of X : Profit of Y = 6 : 5 (as we are assuming that profit is proportional to the investment)

total Profit = Rs.26400

Hence, Profit of X = 26400 * 6/11 where 11 = 6+5 . Is this clear?

**a : b = 6 : 5**and**a+b = 10**then a = 10 * 6/11 and b = 10 * 5/11 where 11 = 6+5

In this question, investment of X : investment of Y = 6 : 5

Hence, Profit of X : Profit of Y = 6 : 5 (as we are assuming that profit is proportional to the investment)

total Profit = Rs.26400

Hence, Profit of X = 26400 * 6/11 where 11 = 6+5 . Is this clear?

Namitha

2013-09-20 23:49:02

Let

If a + b = 10,

6k + 5k = 10

=> 11k = 10

=> k = 10/11

Hence, a = 6*10/11 and b = 5*10/11

No need to remember this derivation.

a = 10 * 6/11 and b = 10 * 5/11

**a : b = 6 : 5**

Then a = 6k and b = 5k where k is a constantIf a + b = 10,

6k + 5k = 10

=> 11k = 10

=> k = 10/11

Hence, a = 6*10/11 and b = 5*10/11

No need to remember this derivation.

**if a : b = 6 : 5**and**a+b = 10,**we can always directly takea = 10 * 6/11 and b = 10 * 5/11

Add a new comment... (Use Discussion Board for posting new aptitude questions.)

Name:

Email: (optional)

6 + 0 =
(please answer the simple math question)

Post Your Comment